Tissue specificity of (E)-β-farnesene and germacrene D accumulation in pyrethrum flowers. (July 2021) - Li, Jinjin; Hu, Hao; Chen, Yu; Xie, Jing; Li, Jiawen; Zeng, Tuo; Wang, Manqun; Luo, Jing; Zheng, Riru; Jongsma, Maarten A.; Wang, Caiyun
Abstract: Plant defensive mimicry based on the aphid alarm pheromone ( E )-β-farnesene (EβF) was previously shown to operate in Tanacetum cinerariifolium (Asteraceae) flowers. Germacrene D (GD), is another dominant volatile of T. cinerariifolium flowers and may modulate both defense and pollination. Here, we find that the increase in GD/EβF ratio at later developmental stages is correlated with the tissue distribution in the flower head: the total content of EβF and GD is similar, but GD accumulates comparatively more in the upper disk florets. Naphthol and N, N -dimethyl- p -phenylenediamine dihydrochloride (NADI)-stained purple ducts containing EβF and GD, were observed in the five petal lips of the corolla and two-lobed stigma of disk florets. By contrast in the peduncle, EβF accounts for nearly 80% of total terpenes, compared to 5% for GD. EβF is accumulated inside inner cortex cells and parenchyma cells of the pith in young peduncle. This is followed by the formation of terpene-filled axial secretory cavities parallel to the vascular bundles. In conclusion, the observed developmental and diurnal emissions of different EβF/GD ratios appear to be regulated by their tissue distribution. Graphical abstract: Image 1 Highlights: EβF and GD are the dominant volatiles with similar contents in pyrethrum flowers. GD accumulates comparatively more in the upper disk florets. EβF and GD were observed in the five petal lips of the corolla and two-lobed stigma of disk florets. In peduncle, EβF was accumulated in the cortex cells and further stored in the secretory ducts.